FAKTOR - FAKTOR PENYEBAB TERJADINYA KARIES PADA IBU-IBU PENGUNJUNG POSYANDU MELATI 1 DESA SENDANG MULYO KECAMATAN NGAWEN KABUPATEN BLORA - Ni Ketut Nuratni (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Background: The high prevalence of dental and oral diseases, especially diseases of cavities (caries) and inflamation of the gums (gingivitis) is influented by various foctors such as heredity, environment, and community behavioral health services.Obiective: Knowing the factors - factors that cause caries in the mother - mother IHC visitors Bed I Mulyo spring village, District. Ngawen, Blora.Methods: This study is a case study that analyzed descriptively in 40 mothers visitors IHC Bed I Mulyo spring village, District. Ngawen, Blora.Result: The various factors that cause dental caries in the mother - mother IHC Visitors Bed I Mulyo Spring Village District of Ngawen Blora district, among others, the factors: Value OHI-S mostly bad criteria (50%), the value of DMF-T  high kateegori average-average of 6.2, the pH of plaque largely by the degree of acidity in plaque pH≤5,5 critical namely 37.5%. While the external factors, namely: environmentil factori show a Iarge part of the drinking water wells fluornya unknown content (95%), 90% Habit Factor like snacking or eating a meal that is sweet and easily attached, health care factors indicate ta 100% of respondents stated never performed oral health education both from the health center, hereditary factors that determine the incidence of caries because 10% of them and the father / mother of his have tabled crowding .Conclusion: The various factors that cause dental caries in the mother - mother IHC Visitors Bed I Mulyo Spring Village District of Ngawen Blora with the highest percentage: Role of health centers can not be implemented properly, the second: a large part of the respondents use drinking water from wells that unknown content,  the third, fourth: PHC distance away from the village spring Mulyo, fifth: people,s behavior in brushing the teeth of time is not true that brushing teeth while bathing.